Relationship Between Overnutrition Status with Physical Activity and Fast Food Consumption at Pasundan 2 Senior High School Bandung - Pritha Pitaloka; Adila Nurhadiya; Insyira Putri (STIKes Budi Luhur Cimahi, 2025)
Adolescence is a time of many preferences, including changes in dietary habits that affect nutritional health. Fast foods are popular food choices among teens due to their availability and practical value but if excessively consumed it can lead to health issues such as being overweight and obesity. Another challenge in digital era, teenager lacked in physical activity. Good physical activity increases energy expenditure, and more frequent exercise helps balance energy intake from food. Both have emerged as concerns due to increasing cases of overnutrition among adolescents, especially those who live in a big city. This study used a cross-sectional design with 188 randomly selected students of SMA Pasundan 2 Kota Bandung. The aim of the study is to evaluate fast food consumption, physical activity and their relationship to student’s nutrition status. Food consumption assessed with Food Frequency Questionnaire (FFQ), while physical activity and nutritional status were measured with Global Physical Activity Questionnaire (GPAQ) also to calculate Body Mass Index (BMI). Among 151 students who frequently ate fast food, 80 (42.5%) overnourished, and 71 (37.2%) had normal nutrition status. 37 students who ate fast food less often, 23 (12.2%) had normal nutrition status, 14 (7.5%) were overnourished. 67 students (35.6%) who frequently ate fast food and had good nutrition mostly engaged in physical activities. Additionally, 48 students (25.5%) who frequently ate fast food but had poorer nutrition were also more likely had high physical activities. Statistical analysis showed no significant relation between fast food consumption and overnutrition (p = 0.09). However, there was a significant association between overnutrition and physical activity levels (p = 0.01).